PENGARUH STRESS DAN TINGKAT KEPUASAN KERJA TERHADAP KOMITMEN KARYAWAN STUDI KASUS PT. FEI - Tarmizi, Achmad; Dewi, Suryani Supra (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The purpose of this study to determine the effect of stress and job satisfaction on employees commitment of PT. FEI. The method used in this study is quantitative, by distributing questionnaires to 100 randomly selected employees. Analytical techniques use path analysis with the help of LISREL program. The result of this study found that job stress had a positive effect on job satisfaction (p-value